Influence of radiation diurnal variation on the rapid intensification process of super Typhoon Rammasun (1409) in the South China Sea - Zhang, Xinghai; Wei, Na; Wang, Qian (Frontiers in Earth Science, 2022)
In this study, a sensitivity experiment based on a numerical model is conducted to study the influence of the diurnal variation of radiation on the rapid intensification process of Super Typhoon Rammasun (1409) in the South China Sea. The result shows that changing the radiation process can change the onset time of the rapid intensification process of the typhoon and its maximum intensity. Vertical wind shear is a key factor in the TC rapid intensification influenced by diurnal radiation cycle, and the diurnal variation of radiation process causes obvious diurnal variation in vertical wind shear by changing the thermal difference between sea and land. The oscillation of vertical wind shear promotes the diurnal variation of the typhoon rainband, with an opposite variation trend in the control and sensitivity experiments, affecting local convective available potential energy and inward transport of entropy and thus influencing the onset time of deep convective in the typhoon inner core region. By changing the establishment of the typhoon warm core (especially the upper-level warm core), deep convections finally affect the rapid intensification of the typhoon. In conclusion, as one of the dynamic factors, vertical wind shear plays a key role in the influence mechanism of the diurnal variation of radiation on offshore typhoon activities.